Determine the bacterial resistance of Streptococcus sobrinus to antibiotics - Saleh Abdulhussain, Hanan; K.A. Al-Hassani, Mithal ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Antibiotics are chemical compound produced by microorganism that kill, or inhibits the growth of the other microorganism. Antibiotics are divided into two types based on their action: bacteriostatic antibiotics, such as tetracycline, and bactericidal antibiotics, such as penicillin. The study aimed was to determine bacterial resistance of S. sobrinus to antibiotics and detect resistance genes. The results for S. sobri nus showed that 41.6% of isolates formed biofilms, and 58.3% were non-biofilm-forming. The results show a clear variation in resistance and sensitivity to antibiotics. S. sobrinus isolates showed 100% complete resistance to amoxicillin. These isolates also showed high resistance to tetracycline and ampicillin (75%), and 66.67% resistance to ciprofloxacin. The isolates showed sensitivity to s (91.67%), erythromycin (50%), gentamycin (41%), cls (66.67%), and hls (75%).